Expectations vs. Abilities: Bridging the Gap - Martin, Mary Andrews (Journal of Applied Business and Economics, 2024)
The purpose of this grounded theory study which applies qualitative techniques, using open-ended interviews and surveys, is to address the problem that businesses lack efficient and effective work production due to entry-level employees not being adequately prepared. The specific purpose is to understand what deficits currently exist between demands and abilities, and what can be done to eliminate those. While there is always some on-the-job training, having this knowledge will fill the current gap in the literature and better prepare entry-level practitioners. While this study looks specifically at accounting students, it can be applied to all areas of business.